Urgent issues and prospects at the intersection of culture, memory, and witness interviews: Exploring the challenges for research and practice. (19th December 2021) - Hope, Lorraine; Anakwah, Nkansah; Antfolk, Jan; Brubacher, Sonja P.; Flowe, Heather; Gabbert, Fiona; Giebels, Ellen; Kanja, Wangu; Korkman, Julia; Kyo, Akira; Naka, Makiko; Otgaar, Henry; et al.
Abstract: The pursuit of justice increasingly relies on productive interactions between witnesses and investigators from diverse cultural backgrounds during investigative interviews. To date, the role of cultural context has largely been ignored by researchers in the field of investigative interviewing, despite repeated requests from practitioners and policymakers for evidence‐based guidance for the conduct of interviews with people from different cultures. Through examining cultural differences in human memory and communication and considering specific contextual challenges for investigative interviewing through the lens of culture, this review and associated commentaries highlight the scope for considering culture and human diversity in research on, and the practice of, investigative interviewing with victims, witnesses, and other sources. Across 11 commentaries, contributors highlight the importance of considering the role of culture in different investigative interviewing practices (e.g., rapport building, questioning techniques) and contexts (e.g., gender‐based violence, asylum seeking, child abuse), address common areas of cultural mismatch between interviewer–interviewee expectations, and identify critical future routes for research. We call for an increased focus in the investigative interviewing literature on the nature and needs of our global community and encourage constructive and collaborative discussion between researchers and practitioners from around the world to better identify specific challenges and work together towards evidence‐based solutions.